Relationship between electrical and mechanical properties of motor units. Issue 4 (April 1990) - Vogt, T; Nix, W A; Pfeifer, B
Abstract : In six healthy volunteers, the size of the motor unit action potential (MUAP) was related to its contractile behaviour. Electrical activity was determined by measuring amplitude and area of the potential, using the macro electromyography (EMG) technique. The mechanical response was characterised by contraction time, twitch force and relaxation time, recorded with the spike triggered averaging technique. With increasing tension of the whole muscle corresponding to an increasing threshold, the force of single units enlarged exponentially compared to their EMG. There was only a weak relationship between contraction time and electrical activity and none between EMG and relaxation time.